A comparative analysis of metaphorical expressions used by rural and urban Ndebele speakers: the contribution of S'ncamtho - Ndlovu, Sambulo (Linguistics, 2019)
This thesis explores language expansion and change through metaphorical expressions that originate with urban youth varieties. It focuses on the impact of S'ncamtho, an Ndebele-based urban youth variety of Bulawayo in Zimbabwe along the variables of rural/urban, sex, age and level of education. The thesis uses Cognitive Metaphor Theory to build on research on metaphor in urban youth varieties to answer the overarching question; how is S'ncamtho impacting Ndebele? It confirms that sex and sexuality, music and partying, love and relationships are popular themes in S'ncamtho. The thesis identifies relexicalisation and replacement of metaphoric vehicles as the main metaphor derivational strategies in S'ncamtho and confirms the existence of clearly discernible genres of metaphor in S'ncamtho which are proverbs, sayings, aphorisms and euphemistic metaphors. While S'ncamtho and other youth varieties in Africa have been identified as urban varieties, the study brings in the dimension of measuring the spread of S'ncamtho to peri-urban and rural areas. Data from questionnaire tests, interviews and observations is analysed using the Idiom Familiarity and Comprehension Judgement Method to measure the impact and spread of S'ncamtho metaphors. The guiding theory in evaluating the spread of S'ncamtho metaphors is a Social Psychology framework- Social Impact Theory (SIT). The thesis argues that S'ncamtho metaphors spread outside Bulawayo’s high density male youth to female and older Ndebele speakers in and outside the city, it identifies male youth in the age cohort 15- 35 years as more familiar and using more S'ncamtho metaphors compared to females and older males in urban, peri-urban and rural areas. It also reveals that S'ncamtho metaphor familiarity declines with age and distance from Bulawayo, and that generally females use less S'ncamtho compared to males and the young are more familiar with S'ncamtho compared to adults. The research reveals that there is no significant difference between rural and urban professionals in S'ncamtho metaphor familiarity and this confirms that improved communication networks impact on the spread of S'ncamtho as professional people frequent Bulawayo for pay and other services. However, the study also noted that there are still more people who have negative attitudes towards S'ncamtho, compared to those who view its impact positively. The thesis argues that the popularity of S'ncamtho has seen S'ncamtho metaphors operating in professions including journalism, health professions, teaching and religious professions. Furthermore, attitudes are changing as some people have begun to view S'ncamtho positively outside the criminal prejudices.